Biomagnetic fluid flow past a stretching/shrinking sheet with slip conditions using lie group analysis - Murtaza, M. G.; Tzirtzilakis, E. E.; Ferdows, M. (AIP conference proceedings, 2019)
The purpose of this paper is to investigate the boundary layer flow and heat transfer of biomagnetic fluid over a stretching/shrinking sheet in the presence of magnetic dipole. We use Lie group transformation to develop similarity transformation. Using this special form of transformation namely Lie group transformation, the governing nonlinear partial differential equations are reduced into a system of couple nonlinear ordinary differential equations subject to associated boundary conditions. The reduced resulting equation are then solved numerically by using MATLAB routine boundary value problem solver bvp4c. The effects of the pertinent parameters such as ferromagnetic parameter, suction parameter, stretching parameter and momentum slip parameter on the flow field and temperature as well as skin friction coefficient and heat transfer rate are presented and discussed through graphically in this study. Results indicate that the dual solutions exits for some specific range of governing parameter. The results of the present study have been compared with those reported by previous results and found a very good agreement that supports the validity of the present analysis and the accuracy of our numerical computations.